2021
DOI: 10.21577/0100-4042.20170793
|View full text |Cite
|
Sign up to set email alerts
|

Síntese De Novos 1,2,3-Triazóis Inspirados No Srpin340 E Avaliação De Seus Efeitos Em Linhagem Celular De Glioblastoma Humano

Abstract: SYNTHESIS OF NOVEL 1,2,3-TRIAZOLES INSPIRED ON THE SRPIN340 AND EVALUATION OF THEIR EFFECTS ON HUMAN GLIOBLASTOMA CELL LINE. It is herein described the synthesis of a series of thirty novel 1,2,3-triazole1,4-disubstituted compounds inspired on the known SRPKs inhibitor N-(2-(piperidin-1-yl)-5-(trifluoromethyl)phenyl)isonicotinamide (SRPIN340) and biological evaluation of them against human glioblastoma multiforme cell line U87MG. Starting with 1-fluoro2-nitro-4- (trifluoromethyl)benzene (1), the substances we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Extending our analysis to other compounds examined by Sousa et al 34 , namely 6B to 6K (identified by Sousa et al. 34 as compounds 8 to 17), we found that these compounds did not substantially affect cellular growth of the U87MG lineage. This discrepancy in cytotoxicity can be primarily attributed to the choice of cell lineage, with U87MG cells representing human glioblastoma cells and L929 cells representing mouse fibroblasts.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Extending our analysis to other compounds examined by Sousa et al 34 , namely 6B to 6K (identified by Sousa et al. 34 as compounds 8 to 17), we found that these compounds did not substantially affect cellular growth of the U87MG lineage. This discrepancy in cytotoxicity can be primarily attributed to the choice of cell lineage, with U87MG cells representing human glioblastoma cells and L929 cells representing mouse fibroblasts.…”
Section: Resultsmentioning
confidence: 62%
“…The impact on cell viability varied when these compounds were applied to different cellular lineages and disease models. Notably, the cytotoxicity observed for compound 6A on L929 cells differed from its effect on the U87MG lineage, where there was no perceived cytotoxicity and cellular viability even showed an increase 34 . Extending our analysis to other compounds examined by Sousa et al 34 , namely 6B to 6K (identified by Sousa et al.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Esses achados estão de acordo com os de outros estudos, onde compostos sintetizados inspirados no SRPIN340 também mostraram citotoxicidade significativa contra células de glioblastoma, melanoma e leucemia (MOREIRA et al, 2018;SOUSA et al, 2021;SIQUEIRA et al, 2017). Essa maior citotoxicidade dos compostos análogos a SRPIN340 pode ter relação com a já relatada baixa potência de SRPIN340, conforme vista em estudos anteriores (GAMMONS et al, 2014;SIQUEIRA et al, 2020).…”
Section: Discussionunclassified